Rational Energy Band Alignment and Au Nanoparticles in Surface Plasmon Enhanced Si‐Based Perovskite Quantum Dot Light‐Emitting Diodes. Issue 19 (15th July 2018) - Liu, Jingjing; Zhang, Xianju; Ji, Yang; Sheng, Xuexi; Ma, Haiguang; Xu, Xiangxing; Yu, Linwei; Xu, Jun; Chen, Kunji
Abstract: Combining inorganic perovskite quantum dots (IPQDs) devices with Si platform is an interesting topic since it is helpful for realizing the optoelectronic integration as well as the multiple‐functional electronics in a compact and lightweight format. However, the poor energy band alignment between the IPQDs and Si limits the device performance, such as the emitting efficiency. Here, a light‐emitting diodes (LEDs) structure is proposed by inserting a poly‐TPD (poly[ N, N ′‐bis(4‐butylphenyl)‐ N, N ′‐bis(phenyl)‐benzidine]) layer between the n‐type IPQDs and the p‐type Si substrate. The light‐emitting diode based on CsPbI3 quantum dots reaches an output power density of 1.68 mW cm −2 with external quantum efficiency of 0.91%, which is enhanced by 34‐fold compared with the reference device. Similar emission enhancement is also observed in the device based on CsPbBr3 quantum dots but the output power density is only 0.6 mW cm −2 . In order to further improve the emission intensity of CsPbBr3 quantum dots devices, Au nanoparticals (Au NPs) are introduced into the hole injection layer, the output power density increases to 1.2 mW cm −2, which is induced by the localized surface plasmon resonance coupling between Au NPs and CsPbBr3 excitons. The results demonstrate that high‐efficiency and stable Si‐based perovskite LEDs can be realized by rational optical and electronic design. Abstract : Silicon‐based perovskite quantum dot light‐emitting diodes are achieved. The performances of green and red diodes are all improved by inserting a poly‐TPD layer. After introducing Au nanoparticles into the device, the performance of green diode is further improved due to localized surface plasmon resonance effect. As shown, high‐efficiency Si‐based perovskite light‐emitting diodes can be realized by rational optical and electronic design.